A NOVEL MICROBIALLY-DERIVED PROTEIN CAN BE EXPRESSED INLACTOCOCCUS LACTIS AND DELIVERED ORALLY TO IMPROVE GUT BARRIER FUNCTION AND PREVENT FIBROGENESIS BY INTERACTING WITH THE EXTRACELLULAR MATRIX DURING GI INJURY. (22nd January 2022) - La Chat, Chip La; Nigatu, Eskedar; Messner, Elisabeth; Raja, Bernat Baeza; Desnoyer, Jill; Johnson, Amy Jo; Willcoxon, Michi; Banas, Stefanie; Han, Andrew; DeSantis, Todd; Dabbagh, Karim; Shilova, Irina; et al.
Abstract: Intestinal barrier dysfunction or the loss of the epithelial integrity allowing the permeation of microorganisms, dietary antigens and other particles into the gastrointestinal (GI) mucosa results in the activation of the immune system and drives inflammation during IBD. Ongoing inflammation in the GI tract and loss of the mucosal barrier are key features of active disease and predict relapse and serious complications. Existing drugs approved in IBD have limited effects on endoscopic remission and improvement in mucosal healing, driving a critical need for therapies which lead directly to mucosal healing. We have identified a microbial protein, SG-2-0776, that directly improves barrier function and reduces fibrogenesis in vitro and in vivo with potential to become a driver of mucosal healing. SG-2-0776 was identified through a novel algorithm, multi-technology meta-analysis (MTMA), using mucosal biopsies from UC patients and control subjects. Two bacterial strains, Eubacterium eligens and Roseburia hominis were significantly reduced in UC samples. Screening of proteins predicted to be secreted from these strains using in vitro transepithelial/endothelial electrical resistance (TEER) and wound healing assays, identified SG-2-0776, a novel protein, which significantly improved epithelial barrier integrity and reduced fibrogenesis. Administration of recombinant SG-2-0776 protein showed improvement in intestinal barrier function, reduced inflammation and fibrosis in rodent models of colitis. Moreover, SG-2-0776 was expressed in Lactococcus lactis as a delivery vehicle and administered orally to act locally for therapeutic effects in these models of colitis. Mechanism of action studies demonstrated that SG-2-0776 interacts with extracellular matrix proteins regulating myofibroblasts differentiation, leading to reduced fibrogenic phenotypes. Altogether, these results demonstrate SG-2-0776 has the potential, as a standalone or adjunct therapy to existing treatments, to ameliorate mucosal barrier function and prevent fibrogenesis in IBD patients.